A imunidade tributária prevista no art. 156, §2º, I, da Constituição Federal e os aspectos controversos do ITBI, em razão do julgamento do Tema 796/STF - Martins, Graziela Mitsue Uemoto Maciel (2024)
This study, utilizing bibliographical, legislative, and jurisprudential research, investigates the Supreme Federal Court (STF, in Portuguese) precedent established in the judgment of RE nº 796.376/SC, evaluated under general repercussion (Theme 796/STF), regarding to the tax immunity outlined in the Article 156, § 2º, I, of the Federal Constitution (CF, in Portuguese), as well as the implications resulting of this understanding in the recent judgments by various Courts of Justice in Brazil. In doing so, it was realized an examination of the constitutional structure and the national tax system derived from it, which were designed to enable the collection of tax revenues, essential for state functions, as well as social rights realization, but without neglecting the taxpayer’s protection based on constitutional principles and on tax immunity rules, which limit the state’s competence for arbitrary tax demands. Therefore, based on these premises, a study was conducted on the conforming aspects of the Tax on Transfer of Real Estate (ITBI, in Portuguese) incidence hypothesis, as well as the constitutive elements of the tax rule under analysis, also considering the institutes and concepts originating from the private law, in order to verify to what extent they were observed or not by the STF, in the judgement of Theme 796. Finally, considering the assumptions established in the STF precedent, it was verified how this understanding has been applied by several Courts of Justice in the country. The results achieved confirm the complexity and practical challenges resulting from the misinterpretation of the constitutional rule, which will, certainly, require that the matter is submitted again to the STF analysis, so that clearer limits can be established about the adequate interpretation and tax immunity application, outlined in the art. 156, §2º, I, of the CF